Dietary mannan oligosaccharide ameliorates cyclic heat stress-induced damages on intestinal oxidative status and barrier integrity of broilers. (21st April 2019) - Cheng, Y F; Chen, Y P; Chen, R; Su, Y; Zhang, R Q; He, Q F; Wang, K; Wen, C; Zhou, Y M
ABSTRACT: This study investigated protective effects of mannan oligosaccharide (MOS) inclusion on growth performance, intestinal oxidative status, and barrier integrity of cyclic heat-stressed broilers. A total of 240 one-day-old chicks were allocated into 3 treatments of 10 replicates each. Control broilers reared at a thermoneutral temperature were fed a basal diet, whereas broilers in heat stress and MOS groups raised at a cyclic high temperature (32 to 33°C for 8 h/d) were given the basal diet supplemented with 0 or 250 mg/kg MOS, respectively. Compared with control group, heat stress decreased ( P < 0.05) average daily gain and feed conversion ratio during grower, finisher, and entire periods, average daily feed intake during finisher and entire periods, and ileal superoxide dismutase activity at 42 D, whereas increased ( P < 0.05) rectal temperature at 21 and 42 D and jejunal malondialdehyde content at 42 D. Dietary MOS increased ( P < 0.05) average daily gain, average daily feed intake, and feed conversion ratio during finisher and entire periods, but decreased ( P < 0.05) jejunal malondialdehyde concentration of heat-stressed broilers at 42 D. Heat stress decreased ( P < 0.05) jejunal villus height (VH) and claudin-3 gene expression at 21 D, and VH and VH: crypt depth (CD) ratio in jejunum and ileum as well as mRNA abundances of jejunal mucin 2 and occludin, and ileal mucin 2, zonula occludens-1, and occludin, and claudin-3 at 42 D, whereas increased ( P < 0.05) serum D-lactate acid content at 21 and 42 D, and serum diamine oxidase activity and jejunal CD at 42 D. The MOS supplementation increased ( P < 0.05) jejunal VH at 21 D, VH and VH: CD of jejunum and ileum at 42 D, mRNA abundances of jejunal occludin and ileal mucin 2, zonula occludens-1, and occludin at 42 D, whereas reduced ( P < 0.05) ileal CD at 42 D. These results suggested that MOS improved growth performance, and oxidative status and barrier integrity in the intestine of broilers under cyclic heat stress.